2015
DOI: 10.1186/s12876-015-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a clinical risk index for advanced colorectal neoplasia among a North American population of screening age

Abstract: BackgroundA clinical risk index employing age, sex, family history of colorectal cancer (CRC), smoking history and body mass index (BMI) may be useful for prioritizing screening with colonoscopy. The aim of this study was to conduct an external evaluation of a previously published risk index for advanced neoplasia (AN) in a large, well-characterized cohort.MethodsFive thousand one hundred thirty-seven asymptomatic persons aged 50 to 74 (54.9 % women) with a mean age (SD) of 58.3 (6.2) years were recruited for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Of those, 50 records were excluded due to the inclusion and exclusion criteria. Finally, a total of 22 studies [28293040414243444546474849505152535455565758] were included, which evaluated 17 different risk scores. Detailed information of the selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 50 records were excluded due to the inclusion and exclusion criteria. Finally, a total of 22 studies [28293040414243444546474849505152535455565758] were included, which evaluated 17 different risk scores. Detailed information of the selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recently published Canadian work showed that the risk index for advanced neoplasia using age, sex, family history of CRC, smoking history and BMI, as derived by Ruco et al[ 55 ], was less predictive of advanced neoplasia in the population of screening age in North America.…”
Section: European Colorectal Screening Scoring Systemmentioning
confidence: 99%
“…A study performed on 1537 asymptomatic patients showed a prevalence of advanced neoplasia, which included cancer or a tubular adenoma, traditional serrated adenoma or sessile serrated adenoma with villous characteristics, and/or high-grade dysplasia and/or diameter ≥10 mm, of 6.8%. [ 19 ] The treatment is usually electrocautery removal performed through colonoscopy, like in our case. A rare, but important complication of giant polyps can be intussusception, as in the 2 cases presented by Avandipo.…”
Section: Discussionmentioning
confidence: 99%